Factores que contribuyen a la resistencia de la ceftriaxona en pacientes posquirúrgicos de apendicitis aguda una revisión sistémica - Pasto Pasto, Rubén Darío (2026)
ABSTRACT: This research analyzes the factors that contribute to ceftriaxone resistance in post-surgical patients with acute appendicitis, through a systematic review of scientific literature published in the last five years. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology was used for the search, selection and analysis of studies in databases such as PubMed, SciELO, Google Scholar and Scopus. Inclusion criteria focused on relevant studies, with full text in English or Spanish, focused on ceftriaxone resistance in surgical settings. The main factors identified included inappropriate use of empirical antibiotics, self-medication, nosocomial infections and the absence of protocols based on microbiological cultures. The prevalence of resistant strains such as E. coli and Pseudomonas aeruginosa is highlighted, as well as physiological conditions such as hypoalbuminemia that affect treatment efficacy. The research concludes that the optimization of personalized antibiotic protocols, the rational use of ceftriaxone and the implementation of local educational and microbiological strategies are essential to improve postoperative clinical outcomes and contain antimicrobial resistance in patients with acute appendicitis.